Analysis of Housing Credit Financing Between Commercial Banks and Sharia Banks - Muhammad Al Mighwar; Salma Hasna Mumtaz (Al-Arfa: Journal of Sharia, Islamic Economics and Law, 2023)
This study tries to compare the housing loan financing system between commercial banks and Islamic banks. The purpose of this comparison is to find out the differences in the housing loan financing system by Bank Mandiri KCP Majalaya and Bank Syariah Indonesia (BSI) as samples. Many people know that conventional banks use interest rates which are used as interest and Islamic banks do not use them. This analysis compares the conditions that apply, the Housing Loan process is implemented, the Akad or Initial Requirements, Installment Calculations, and the care of customers who are late paying or paying prematurely. Based on the analysis that has been done, it can be concluded that the comparison of lending to Mandiri Conventional Banks and Murabahah Financing at Indonesian Sharia Banks has many similarities in the procedures and requirements files. It's just that the Akad/agreement aspect has a difference. Conventional Banks fully use the Interest System. Meanwhile, Islamic Banks apply a Murabahah Contract with a profit sharing system from service profits and real transactions.